2020
DOI: 10.1002/pon.5546
|View full text |Cite
|
Sign up to set email alerts
|

Fear of cancer recurrence in patients with multiple myeloma: Prevalence and predictors based on a family model analysis

Abstract: Objective Fear of cancer recurrence (FCR) is a common psychosocial sequela among cancer survivors, but data on patients with multiple myeloma are scarce. This study calculated the prevalence of FCR and identified family and social factors that predict FCR in the study population. Methods We recruited 127 myeloma patients and their partners to participate in a cross‐sectional survey from a regional tertiary cancer centre in China. The questionnaires included items on demographic characteristics and from the fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 29 publications
1
32
1
Order By: Relevance
“…Due to the FoP, patients will have large emotional fluctuations, which will eventually affect the treatment effect and quality of life. At present, there are few studies on FoP in lung cancer patients in China (9), and in this study we hoped to develop an understanding of its relationship with QOL in lung cancer patients to increase awareness in medical settings and the community. We present the following article in accordance with the SURGE reporting checklist (available at https://dx.doi.org/10.21037/ apm-21-2821).…”
Section: Original Articlementioning
confidence: 99%
“…Due to the FoP, patients will have large emotional fluctuations, which will eventually affect the treatment effect and quality of life. At present, there are few studies on FoP in lung cancer patients in China (9), and in this study we hoped to develop an understanding of its relationship with QOL in lung cancer patients to increase awareness in medical settings and the community. We present the following article in accordance with the SURGE reporting checklist (available at https://dx.doi.org/10.21037/ apm-21-2821).…”
Section: Original Articlementioning
confidence: 99%
“…Caregiver FCR was unrelated to survivor communication [60]. There were somewhat inconsistent associations with caregiver social support/constraint, with 4/6 studies finding no association [30,52,56,74], but one study finding a negative association with social support [53] and another finding a positive association [33].…”
Section: Patient-caregiver Relationshipmentioning
confidence: 99%
“…There were negative associations with the meaning of illness [4,58]. Two studies found no association with family hardiness [4,52,56].…”
Section: Psychologicalmentioning
confidence: 99%
“…This finding is similar to those obtained for patients with multiple myeloma (57.65 ± 7.73) and inflammatory bowel disease (58.61 ± 5.95) in China. 9,10 There are two possible explanations for this finding. First, the above three diseases may share several similar characteristics, such as a long disease course, frequent recurrence, and incurability.…”
Section: Discussionmentioning
confidence: 99%
“…7 The Resiliency Model of Family Stress posits that family hardiness is an important resistance and a family resource that plays a fundamental role in successful adaptation. 8 Previous studies have shown that higher levels of family hardiness are associated with lower levels of fear of disease recurrence, 9 higher levels of psychological resilience, and more successful family adaption. 8,10,11 However, within the medical domain, most studies about family hardiness have tended to focus on families with ill or disabled children or patients with malignant tumors rather than those with common chronic diseases such as HF, chronic obstructive pulmonary disease, and diabetes.…”
Section: Introductionmentioning
confidence: 99%